Effect of high‐concentrate diets on mRNA expression of genes related to muscle fiber type and metabolism of psoas major muscle in goats. (4th May 2022) - Ren, Qijun; Li, Hanmei; Xu, Fengping; Zhu, Yihan; Zhang, Xiangying; Fan, Tingting; Wei, Zhangyi; Yuan, Feifan; Han, Fei; Cong, Rihua
Abstract: In the process of modern breeding, high‐concentrate diets are widely used to meet the high energy nutritional requirements of animals but change the form of access to energy and nutrients and the way the organism metabolizes them. Goat psoas major (PM) muscle is a hybrid skeletal muscle whose characteristics are important for the motility and meat quality of goats. However, there are few studies on the effects of high‐concentrate diets on the muscle type and metabolic characteristics of PM in goats. In this study, two treatment groups were set up: high concentrate group (HC) and control group (C). The expression of genes related to muscle type and metabolism of the PM was examined by quantitative PCR. The results showed that high concentrate promoted the conversion of PM fibers from intermediate to slow type at the mRNA level, improved the absorption, transport, and oxidation of fat by PM, and upregulated the expression of calpain system. These changes may be regulated by the involvement of differential expression of MSTN, Myf‐5, and IGF‐2 . These results suggest that high concentrate may exert a positive effect on skeletal muscle function, metabolism, and meat quality in goats by affecting the expression of muscle type and metabolism‐related genes.